A Study Of Merger Of Sbi And Associate Banks And Its Probable Impact On Banks, Nagpur - Gondane, Khushbu; Khaire, Megha (Journal of Neonatal Surgery, 2025)
The merger of State Bank of India (SBI) with its associate banks has been one of the most significant events in the Indian banking sector in recent years. This study aims to analyze the merger process, its implications, and the probable impact on banking operations, customers, and the economy in the region of Nagpur. The merger, which brought together SBI with five of its associate banks, is expected to have far-reaching consequences on various facets of banking, including financial stability, service delivery, operational efficiency, and market competition. The research will focus on the potential advantages and challenges faced by SBI post-merger, specifically in Nagpur, a key city in central India. Through a combination of qualitative and quantitative methods, the study will explore how the merger has affected the banking services, customer satisfaction, and employment in the region. Additionally, the study will examine changes in the financial performance of the merged entities and the effects on customer access to banking services, particularly in terms of branch expansion, digital banking, and loan disbursement. In conclusion, the study aims to provide a comprehensive understanding of the long-term effects of the SBI-Associate Banks merger on both the bank's operational capabilities and the banking environment in Nagpur. The findings are expected to offer valuable insights for policymakers, banking professionals, and customers, guiding future decisions regarding bank consolidation and the banking landscape in India.